Predictors of Manual Dexterity in Simulation-Based Cataract Surgery - Palazzolo, Laura; Kozlova, Anna; Laudi, John J.; Rizzuti, Allison E. (Journal of Academic Ophthalmology, 2020)
Introduction The aim of this study is to determine if prior experience with fine motor hobbies influences a surgeon-in-training's performance on a cataract surgical simulator.Materials and Methods Medical students (n = 70) performed navigation, forceps, and capsulorhexis simulations using the Eyesi Ophthalmosurgical Simulator. Participants were surveyed regarding fine motor hobby experiences, including musical instruments, video games, sewing, knitting, origami, painting, crafting, jewelry making, drawing, and extracurricular dissection.Results Medical students with extracurricular dissection experience, including work in research laboratories involving microscopic animal dissection, did significantly better on the forceps simulator task (p = 0.009). Medical students with drawing experience performed better on capsulorhexis (p = 0.031). No other fine motor hobbies were significant for improving simulator scores.Conclusion Drawing and extracurricular dissection lend to improved technical ability on the cataract surgical simulator. This research continues the conversation regarding fine motor hobbies that correlate with microsurgical ability and adds to the growing area of research regarding the selection and training of ophthalmology residents.
Keywords: cataract surgery; resident education; surgical simulator